Bioactive components and molecular mechanisms of Xiaoyao pill in the treatment of chloasma: based on integrated network pharmacology and bioinformatics methods - Suyue PAN; Min HU; Pu WANG; Qiao HUANG; Dongyu CHEN; Hongxin WANG; Xiaoyu YANG; Wenlong FAN; Yuqing HE (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To analyze the active ingredients of Xiaoyao Pill and its molecular mechanisms in the treatment of chloasma. Methods The active ingredients of Xiaoyao Pill, its target proteins and the targets related to human chloasma were searched through BATMAB-TCM database, GeneCards database, CTD database and GEO database, and the network diagram of active ingredient-disease targets was constructed. STRING database was used to construct protein interaction network, followed by GO and KEGG enrichment analysis. Finally, the active ingredients and common targets were verified by molecular docking. Results Xiaoyao Pill contained many key active ingredients such as angelica, 1-methyl-2-dodecyl-4-quinolone, ergotamine, palmitic acid, behenic acid, azelaic acid, and retinol, which possibly regulated expression of proteins related to core genes such as AKT1, INS, TNF, TP53, IL1B, KCNA1, PPARG, and JUN, resulting in the improvement of melasma. KEGG enrichment analysis revealed that the pathways involved in the action of Xiaoyao Pill included neuroactive ligand-receptor interactions, retrograde endocannabinoid signaling, dopaminergic synapses, CAMP signaling, nonalcoholic fatty liver disease, and gonadotropin-releasing hormone secretion. Molecular docking showed that the binding energies of TNF-ergotamine, IL1B-ergotamine, PPARG-ergotamine and JUN-ergotamine were all <-9 kcal/mol. Conclusions In addition to scavenge of free radicals, inhibition of melanin synthesis and anti-aging, Xiaoyao Pill can also inhibit nuclear transcription factor and reduce the inflammatory cascade reaction of IL-1β and tumor necrosis factor-α, resulting in anti-inflammation and antioxidation, consequently leading to improvement of chloasma.